The development of animal form : ontogeny, morphology, and evolution - Minelli, Alessandro (Cambridge University Press, 2003)
The Development of Animal Form integrates traditional morphology and contemporary molecular genetics while incorporating research on postembryonic development. The result is unconventional views of basic animal organization. The book will interest graduate students and researchers of evolutionary and developmental biology, and scholars in cell biology, genetics, and zoology.